Evaluation of the Effects of Carbamazepine-Loaded Chitosan-Coated Plga-Zein Nanoparticles on Pilocarpine-Induced Seizure Model in Zebrafish Larvae: Developmental Toxicity and Behavioral Assays - Özhan, Güneş; Alak, G.; Yıldırım, S.; Ugur Kaplan, A.B.; Köktürk, M.; Nazli, D.; Gözegir, B.; Cetin, M. (Oxford University Press, 2025)
Epilepsy, the most common neurological disorder worldwide, is characterized by sudden paroxysmal brain activity, which can be generalized or focal. Extensive research has explored various treatment strategies for this condition. Our study used a pilocarpine (PL)-induced seizure model in zebrafish (Danio rerio) embryos and larvae to assess the effects of carbamazepine (CBZ)-loaded chitosan-coated PLGA-Zein nanoparticles (NPs) over 96 hr. We evaluated the developmental toxicity (mortality, malformation, and larval hatching), behavioral changes (sensorimotor reflexes), and histopathological and immunohistochemical alterations in brain tissue, focusing on 5-hydroxytryptamine receptor 4 (5HT4), and brain and muscle ARNT-like 1 (BMAL1) expressions. Our findings revealed high mortality and malformation rates in groups treated with pure CBZ (PL + CBZ 50 and PL + CBZ 100). These groups also exhibited delayed hatching and impaired sensorimotor reflexes. In contrast, the CBZ-NP-treated groups (PL + CBZ NP 50 and PL + CBZ NP 100) showed hatching rates comparable with the control group, with significantly lower mortality and malformation rates compared with pure CBZ-treated groups. Moreover, intense cytoplasmic expression of 5HT4 and BMAL1 was observed in neuropils of the PL + CBZ 100 group. This study highlights the potential of CBZ-loaded NPs in reducing developmental toxicity and adverse neurological effects associated with pure CBZ treatment in seizure models. © The Author(s) 2025. Published by Oxford University Press on behalf of the Society of Environmental Toxicology and Chemistry. All rights reserved.
Keywords: Carbamazepine Nanoparticles; Developmental Toxicity; Epilepsy; Neurological Effects; Zebrafish Seizure Model